The effectiveness of information-motivation-behavioural skills model-based diabetes self-management education among patients with Type 2 Diabetes (IMBDSME) : randomized clinical trial - Albelbisi, Zaki (2021)
Aim: to develop and examine the effectiveness of Information Motivational Behavioural Model-based Diabetes Self-Management Education intervention on three self-care activities: diet, physical activity and medications management self-care behaviours, and other outcomes such as quality of life and glycaemic control.